A Model Study on the Generation of Internal Tides by Tidal Flows Over a Submerged Seamount in the Channel (Communications in Computational Physics, 2010)
It is known that the submerged seamount/ridge is a source for the generationof internal tides. In this paper, a three-dimensional two-layer model is set up tostudy the generation of internal tides by tidal flows over a submerged seamount/ridgein the channel. Several numerical experiments with different topographic features,upper layer depths, tidal flows and background currents are carried out to study thevariations of the induced internal tides. It is shown that, for the specific stratification,the seamount feature, the slope, the initial upper layer depth and the imposingdriven force determine the Froude number near the seamount peak. Once when theFroude number is supercritical, the associated maximum amplitude of the induced internaltide is so large that the internal tide begins to disintegrate, which brings aboutsevere variations of the current velocity and the water elevation fields, and the associatedinduced baroclinic tidal energy around the seamount peak is much larger thanthe barotropic one. The Richardson number greater than 1/4 is a criterion for stabilityof shear flow. Since the maximum tidal velocity changes within 0 ∼ 360◦ with timein a period around the seamount peak, the induced internal tide does not stride theseamount peak before it disintegrates, which is different from the two-dimensionalmodeled results. The asymmetrical slope of the submerged seamount is a mechanismfor the asymmetrical internal tide generation.